Wetlands Ecosystem: A Sensitive Landscape of Unorganized Nonadministered Serveces. - Singh I.F.S, Dr.U.V.; Hebale, Deepthi (European Journal of Applied Sciences, 2021)
The association of man and wetlands is ancient, with the first signs of civilization originating in wetland habitats such as the flood plains of the Indus, the Nile Delta and the Fertile Crescent of the Tigris and Euphrates rivers. Evidence of the first wetland traces back to the Ordovician Period (485.4 million to 443.8 million years ago), As much 17.56% of the state’s geographic area (34.74 lakh hectares) has been identified as wetland/waterbodies in the National Wetland Atlas of the Union ministery of environment and forests. A total of 15.26 million hectares have been identified as wetland in India. Gujarat is followed by Andhra Pradesh, Uttar Pradesh, West Bengal and Maharashtra in the order. Even the coastal Union territories of Diu and Daman have upto 18.46% of their total geographical area as wetland, next only to Lakshadweep whose 96.12% of land area is wetland. India has totally 27, 403 wetlands/water bodies, of which 23,444 are inland wetlands and 3,959 are coastal wetlands. According to the Directory of Asian Wetlands (1989), wetlands occupy 18.4% of the country’s area (excluding rivers), of which 70 % are under paddy cultivation. In India, out of an estimated 4.1 million hectares (MHa) (excluding irrigated agricultural lands, rivers and streams) of wetlands, 1.5 MHa are natural, while 2.6 MHa are manmade. To declare any water bodies as wetland, it is manditorily be notified by the Central Government, State Government and Union Territory Administration under the Wetland Rules 2017.Presently there are 41 Ramsar notified wetlands in the country. There is no notified wetlands/ Ramsar wetlands in Karnataka as on date. There is need of hour to introduce panel provisions with Institutional authority in the Wetlands (Conservation and Management) Rules, 2017. Also, provisions for constitution of district level authority shall be made under the Rules with adequate powers for administration, management, development and conservation. Else, there could be more meaningful, if instead Rules, an Act should be promulgated on the lines of Forest (Conservation) Act 1980.